Efficacy of carbon dioxide laser combined with photodynamic therapy in the treatment of chronically infected wounds - Yinfeng Xia; Yongsong Chen; Han Luo; Yu Zhu; Qiang Tan; Ping Wu; Zhiyong Chen (Photodiagnosis and Photodynamic Therapy)
Background: Chronic infected wounds present a significant clinical challenge due to bacterial biofilm formation and antibiotic resistance, which impede healing. Therefore, there is a need to find safe and effective methods to control infection and promote wound healing. Objective: The purpose of this study was to evaluate the efficacy and safety of the combination of carbon dioxide laser and photodynamic therapy in the treatment of chronically infected wounds. Methods: A randomized controlled trial included 121 patients divided into four groups: combination therapy group (n = 31), photodynamic therapy (n = 29), CO2 laser alone (n = 30), and placebo group (n = 31). Wounds were assessed for healing rate, bacterial quantification, blood vessels, collagen content, interleukin-6, and C-reactive protein at baseline and after treatment. Mixed-effects models and repeated-measures ANOVA were used for analysis. Results: The combination group achieved the highest healing rate (80.1 ± 15.2 %, p < 0.001), significantly surpassing the photodynamic group (71.2 ± 19.1 %), laser group (66.0 ± 15.4 %), and placebo group (61.6 ± 18.2 %). Bacterial load reduction was most pronounced in the combination group (2.9 ± 0.9 × 10^9 CFU/mL vs. 5.4 ± 1.1 × 10^9 CFU/mL in placebo, p < 0.001), with photodynamic therapy showing comparable antimicrobial effects. Angiogenesis was markedly enhanced in the combination group (70.7 ± 6.1 vessels/mm² vs. all groups, p < 0.05), alongside reduced interleukin-6 and c-reactive protein levels (p < 0.05). Collagen content differences were nonsignificant overall (p = 0.081), though the combination group (58.5 ± 4.9 %) outperformed laser and placebo (p < 0.05). Conclusion: The efficacy of CO2 laser combined with photodynamic therapy in treating chronic infected wounds are effective, and photodynamic therapy dominates. It promotes wound healing by inhibiting wound bacterial reproduction, reducing inflammatory reactions, increasing the number of blood vessels in the wound, and promoting collagen synthesis.